Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1080/15476286.2022.2078094
|View full text |Cite
|
Sign up to set email alerts
|

The Dihydrouridine landscape from tRNA to mRNA: a perspective on synthesis, structural impact and function

Abstract: The universal dihydrouridine (D) epitranscriptomic mark results from a reduction of uridine by the Dus family of NADPH-dependent reductases and is typically found within the eponym D-loop of tRNAs. Despite its apparent simplicity, D is structurally unique, with the potential to deeply affect the RNA backbone and many, if not all, RNA-connected processes. The first landscape of its occupancy within the tRNAome was reported 20 years ago. Its potential biological significance was highlighted by observations rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 154 publications
0
16
0
Order By: Relevance
“…Recent studies showed that D is the second most prevalent modification in tRNA. 13 , 14 Catalyzed by D synthases (Dus), D is formed by the hydrogenation of uridine (U) whose C5–C6 bond is reduced, and is found within the eponym D loop of tRNAs. 15 , 16 With its unique structure, D can influence the RNA backbone and a series of RNA-involved processes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that D is the second most prevalent modification in tRNA. 13 , 14 Catalyzed by D synthases (Dus), D is formed by the hydrogenation of uridine (U) whose C5–C6 bond is reduced, and is found within the eponym D loop of tRNAs. 15 , 16 With its unique structure, D can influence the RNA backbone and a series of RNA-involved processes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, wet-lab experimental methods such as D sequencing (D-seq) and rhodamine sequencing (Rho-seq) established the presence of D on mRNAs in yeast and human, which further verified its physiological significance. 14 , 23 , 24 Both methods take advantage of D-specific chemistry and next-generation sequencing to determine the location of D across the transcriptome, resulting in high-confidence single-nucleotide-resolution data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dihydrouridine (D) is one of the most abundant post-transcriptional modified bases in the transcriptome [ 1 , 2 , 3 ]. Present mainly in transfer RNA (tRNA) and occasionally in bacterial ribosomal RNA (rRNA), D has recently entered the messenger RNA (mRNA) world [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dihydrouridine (D) is one of the most abundant post-transcriptional modified bases in the transcriptome [ 1 , 2 , 3 ]. Present mainly in transfer RNA (tRNA) and occasionally in bacterial ribosomal RNA (rRNA), D has recently entered the messenger RNA (mRNA) world [ 1 , 2 ]. Indeed, this modification was recently detected in fission yeast mRNAs, including those encoding cytoskeleton-related proteins (2), in Saccharomyces cerevisiae mRNAs [ 4 ], but also in human mRNAs [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%